Medical entomology for students - Service, M. W. (London ; New York : Chapman & Hall, 1996)
Arthropod vectors of disease pose major health problems worldwide. This textbook aims to provide the reader with basic information on the recognition, biology and medical importance of arthropods which affect human health and their control. The book is primarily aimed at students of subjects as diverse as tropical medicine, parasitology, entomology and pest control. It is also intended as a source of information for physicians, nurses, health officials and community health workers.
Easy accessibility, beautiful illustrations and clear presentation combine to make this book essential reading for students and teachers alike of this important subject.
Includes bibliographical references and index.
Keywords: Insects as carriers of disease; Entomology; Insect Vectors -- parasitology; Entomology